Dual Users and Electronic Cigarette Only Users: Consumption and Characteristics - Lee, Alexander S. (Int J Healthc Med Sci, 2018)
BACKGROUND: E-cigarette use has grown in popularity, especially as the devices have been touted as smoking cessation tools. In an exploratory study, we sought to compare dual users (i.e., users of both combustible tobacco and e-cigarettes) to e-cigarette only users. METHODS: The Electronic Cigarette Opinion Survey (ECOS) was employed to assess users' (n=78) perceptions and consumption of e-cigarettes and combustible cigarettes. Quantity of e-juice and nicotine used and time of initial nicotine exposure were assessed. Multivariable logistic regression was used to evaluate the association between e-cigarette use behaviors and being an e-cigarette only user compared to a dual user. RESULTS: Compared to dual users, e-cigarette only users consumed higher levels of nicotine in e-juice (p=0.0009) and more nicotine per month (p=0.03). For dual users, the time of first nicotine exposure after waking was significantly earlier than for e-cigarette only users (mean= 9.6 minutes (SD= 8.0) and mean= 26.6 minutes (SD= 22.0), respectively; p=0.0056). Results from the regression models suggest the amount of e-juice consumed and time of first nicotine exposure after waking are significantly associated with being an e-cigarette only user. CONCLUSIONS: These findings shed light on the perceptions and use patterns of e-cigarette only users compared to dual users. As regulation of e-cigarettes is considered, understanding the impact of e-cigarettes and dual use is imperative. Despite frequent marketing claims that e-cigarettes are completely safe, health campaigns need to convey emerging and mixed findings on safety as well as current scientific uncertainty to the public.